Cadaveric aortic aneurysm creation: A life-like model for training endovascular repair - Peter Osztrogonacz, MD; Bright Benfor, MD; Paul Haddad, MD; Rebecca Barnes, MT; Ponraj Chinnadurai, MBBS, MMST; Vy Dang, MS; John Paul Hess, MS; Stuart J. Corr, PhD; Maham Rahimi, MD, PhD (Journal of Vascular Surgery Cases and Innovative Techniques, 2023)
The recent decline in RAAA incidence and the fast paced scenario with associated challenges regarding training calls for initiative for a better training environment to maximize learning. This led us to the creation of a pulsatile human cadaveric RAAA model. Fresh frozen cadaver was used to create RAAA with BioTissue in hybrid suite with ability to perform CBCTA for sizing. As a proof of concept, the model was used to perform REVAR with proximal CODA balloon control. The model proved to be feasible and we believe it is a better environment to train and gain adequate proficiency in RAAA management.